Nepal : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Requests for Waiver and Modification of Performance Criteria; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Nepal. (IMF Staff Country Reports; Country Report, 2007)
This paper discusses key findings of the Fourth Review Under the Poverty Reduction and Growth Facility (PRGF) for Nepal. The PRGF-supported program is broadly on track. All quantitative performance criteria for the fourth review were met. A number of structural performance criteria and benchmarks have been implemented, albeit with delays. For those that have not been completed, substantial progress has been made. With this, the authorities have requested waivers for four structural performance criteria and completion of the fourth review, as well as modification of performance criteria for the fifth review.